(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article discusses the creation of the play A falecida, by Nelson Rodrigues, seeking to sketch the biographical, literary, cinematographic references, as well as the author’s thematic obsessions, analogies, influences, echoes, patterns and recurring ideas. It also presents a self-referenciality in the textual construction, which were taken into account in the tessitura of his first carioca tragedy. It creates a panel of structural correlations, repetitions, recurrences, displacements and situations between her pieces and the chronicles of A vida como ela é..., as well as brief traces of his poetics and the influence of the city of Rio de Janeiro in the creation of language.